Answers

  • Brainly User
2016-02-04T10:55:35+08:00
Change f(x) = ax² + bx + c to vertex form f(x) = (x-h)² + k.

3x² - 6x + 7     ⇒   a = 3;     b = -6;      c = 7

Solve for h:
    
     h =  \frac{-b}{2a}
     
     h =  \frac{-(-6)}{2(3)}

     h =  \frac{6}{6}

     h = 1

Solve for k:
     k = f(h)

     k = 3 (h)² - 6(h) + 7

     k = 3 (1)² - 6(1) + 7

     k = 3 - 6 + 7

     k = 4

Substitute the values of a, h, and k to vertex form f(x)=a(x-h)² + k
   
ANSWER:  Vertex form     f(x) = 3(x - 1)² + 4

------------------------

Vertex of the parabola: (h, k) = (1, 4)

This means that the parabola (graph of the given quadratic function) opens downward and has a maximum value at vertex (1,4) because  a=3 or 3>0.

0